2020
DOI: 10.1094/phyto-09-19-0370-r
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Cotton Chromosome 11 and 14 Root-Knot Nematode Resistance Quantitative Trait Loci Effects on Root-Knot Nematode Postinfection Development, Egg Mass Formation, and Fecundity

Abstract: Cotton (Gossypium hirsutum) resistance to root-knot nematode (RKN) (Meloidogyne incognita) is controlled by quantitative trait loci (QTLs) on chromosomes 11 (CHR11) and 14 (CHR14). The individual contributions of these QTLs to resistance are not completely understood. We developed near isogenic lines susceptible at both loci (null), having CHR11 or CHR14 alone, and having both QTLs (CHR11/CHR14). RKN reproduction, postinfection development, egg mass formation, and adult female fecundity were evaluated. Total R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The results presented here clearly show the benefits in terms of yield and reduction of M. incognita density of currently available cultivars with at least partial resistance to M. incognita. The HR-PHY resistance, which involves two well described resistance genes (RK1 and RK2) (Da Silva et al, 2019;Gutiérrez et al, 2010;Wubben et al, 2020), in commercial cultivars was superior to commercial cultivars with partial resistance or the DeltaPine source(s) of resistance. The first developed germplasm with high levels of M. incognita resistance in agronomically advanced cotton was Auburn 623 RNR (Shepherd, 1974).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results presented here clearly show the benefits in terms of yield and reduction of M. incognita density of currently available cultivars with at least partial resistance to M. incognita. The HR-PHY resistance, which involves two well described resistance genes (RK1 and RK2) (Da Silva et al, 2019;Gutiérrez et al, 2010;Wubben et al, 2020), in commercial cultivars was superior to commercial cultivars with partial resistance or the DeltaPine source(s) of resistance. The first developed germplasm with high levels of M. incognita resistance in agronomically advanced cotton was Auburn 623 RNR (Shepherd, 1974).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that there are two genes associated with the root-knot nematode resistance in Auburn 623 RNR (Gutiérrez et al, 2010). One gene which is located on chromosome 11 is associated with a reduction in the number of galls and it is involved with a delay or reduction in sedentary second-stage juveniles (J2) which develop in later life stages (Da Silva et al, 2019;Wubben et al, 2020). The second gene, which is located on the small arm of chromosome 14, is associated with a reduction in M. incognita reproduction rate, by reducing the total number of females and compromised egg production in females (Da Silva et al, 2019;Wubben et al, 2020).…”
mentioning
confidence: 99%
“…In the late 2010s, M. enterolobii was discovered in North and South Carolina, and Louisiana (Ye et al, 2013;Rutter et al, 2019;Philbrick et al 2020). Recently, M. enterolobii was intercepted in Louisiana on sweetpotato storage roots imported from North Carolina, confirming previous suspicions of a link between M. enterolobii spread and sweetpotato planting stock (Thiessen, 2018;Rezende et al, 2022). Because of its wide geographical distribution and host range, M. enterolobii is considered an important nematode species and is on the European and Mediterranean Plant Protection Organization (EPPO) quarantine list because of high pathogenicity (Castagnone-Sereno, 2012).…”
mentioning
confidence: 81%
“…The number of eggs per egg mass was equivalent across all lines tested, which indicated GB713-derived resistance does not manifest as a reduction in fecundity. Wubben et al (2020) assessed root-knot nematode development, egg mass formation, and fecundity in near-isogenic lines that carried chromosome 11 and 14 QTLs separately, together, or not at all. This study showed that chromosome 11 QTL acts early in the resistance response to limit feeding site formation and inhibits the early stages of juvenile development.…”
Section: The 2010smentioning
confidence: 99%